ANALISIS HUBUNGAN INFLASI DAN TINGKAT SUKU BUNGA DENGAN HARGA SAHAM PT. INDOFOOD SUKSES MAKMUR DI BURSA EFEK JAKARTA - Rizki Ahmad Fauzi (STIE Binaniaga, 2005)
The price of share is difficult to be predicted because influenced by various factor, like inflation, rate of interest, industrial production, investor interest to risk etc. Specially for the inflation influence and rate of interest to share, this is be required to get attention by investor when they wish to buy or sell share The inflation and rate of interest always make a move to fluctuate and influenced by national economy condition. This matter will influence national economy wheel. After this will represent a cycle The inflation and rate of interest influence the climate and enthusiasm of investment, cost and also the company earnings, because the inflation and high rate of interest will kill effort industrial and commercial sector. So that, this matter affect also at share price. While the inflation and the fair rate of interest will stimulate economic wheel movement because all sector needing capital to fund their company. So that this matter will give advantage for investor This research aim to for analyzing the relation between the inflation and the rate of interest at the price of share by partial or the whole. Data analysis Technique used is quantitative techniques that is look for the level of correlation between the inflation and the rate of interest at the price of share joined by the hypothesis test. Beside that we also use the qualitative technique by using characteristics and facts. Result of analysis show ( 1) there are negative relation and weak between the inflation and the price of share ( 2) there are positive relation and weak between the rate of interest and the price of share (3) there are positive relation and weak between the inflation and the rate of interest with the price of share.